If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + 1) = 2x + -6x Reorder the terms: 6(1 + 3x) = 2x + -6x (1 * 6 + 3x * 6) = 2x + -6x (6 + 18x) = 2x + -6x Combine like terms: 2x + -6x = -4x 6 + 18x = -4x Solving 6 + 18x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 18x + 4x = -4x + 4x Combine like terms: 18x + 4x = 22x 6 + 22x = -4x + 4x Combine like terms: -4x + 4x = 0 6 + 22x = 0 Add '-6' to each side of the equation. 6 + -6 + 22x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 22x = 0 + -6 22x = 0 + -6 Combine like terms: 0 + -6 = -6 22x = -6 Divide each side by '22'. x = -0.2727272727 Simplifying x = -0.2727272727
| (x-6)(x^2+2x-4)=0 | | 5y=15x+20 | | 14x+4y=-76 | | 4.9x+44=19.1 | | 7sinx+5=2cos^2x | | 7x-2(-3x+4)=18 | | 12+(-10)+(-2)= | | 5+45=-5(8x-10) | | (7x+4)=(13x+6) | | 4/60= | | 2(2+j)=4(j+10) | | -7+5-(-10)= | | 5((-1)+3)= | | (3x^2-6x-3)(7x+8)=0 | | 3.1=(10*2.5)+(13*3)+(4*x)/10+12+x | | 9x-6+7x=8x+6 | | 7-(2z-3)=7-3z | | -19-(-21)= | | f(x)=2+4x | | 80+9h=224 | | 4x^6=81 | | 4.3(y+6)=30 | | [2n+5]=11 | | 2(x+7)=10x-10 | | 12+(-57)= | | -3x-2=-4x-8 | | -5x+9=-6x-3 | | 12-7j=-2 | | 12y-3y=7 | | 2(-1+x/3)=12 | | m^2+2m-1m-5m-10+1=0 | | 5+2j=-13 |